Building an agile state-wide research infrastructure to address COVID-19 and emerging threats: insights from an equity-centered public health and academic collaboration in California - Priya B. Shete; Nicole Santos; Hilary Spindler; Tomás León; Maya Petersen; A. Marm Kilpatrick; Seema Jain; James Watt; Rohan Radhakrishna; Erica Pan; Tomás Aragón (Frontiers in Public Health)
The COVID-19 pandemic underscored the need for efficient real-time evidence generation to inform public health interventions and policies. To address this gap, a formalized research partnership between the California Department of Public Health (CDPH) and the University of California (UC) was created. The aim of this case study is to describe the achievements and lessons learned from the California Collaborative for Public Health Research (CPR3). This state-wide infrastructure (1) streamlines data sharing and use between UC researchers and public health agencies; (2) sets priority research agendas that reflect the needs of the state’s diverse communities; and (3) fosters research collaboration and evidence translation. This partnership may serve as a guide for how academic and public health entities can jointly prioritize, conduct, and act upon policy-relevant research for current and emerging threats.